Group dynamics - Donelson R. Forsyth (Thomson/Wadsworth, 2006)
In the Fourth Edition of his best-selling text, Forsyth combines an emphasis on research, empirical studies supporting theoretical understanding of groups, and case studies to illustrate the application of concepts to actual groups thus providing students with the most comprehensive treatment of groups available. Forsyth builds each chapter around a real-life case and draws on examples from a range of disciplines including psychology, law, education, sociology, and political science. Because he tightly weaves concepts and familiar ideas together, the text takes students beyond simple exposure to basic principles and research findings to a deeper understanding of each topic